2021
DOI: 10.1002/cctc.202001775
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Nitrogen Reduction Performance of Si‐doped 2D Nanosheets of Boron Nitride Evaluated via Density Functional Theory

Abstract: Electrochemical nitrogen fixation under ambient conditions is proposed as a sustainable alternative to the traditional Haber‐Bosch method to combat both a global energy crisis and climate change. However, effective catalysts for electrocatalytic nitrogen reduction reaction (eNRR) under ambient conditions, a crucial part for the electrocatalysis system, still face large challenges of low Faradic efficiency (FE) and low yield of ammonia. Here, we propose Si‐doped BN 2D nanosheets (BNNS) as a new class of metal‐f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…Generally, the first hydrogenation step (*N 2 + H + + e − → *N 2 H) is the potential-determining step (PDS) because the triple bond is so strong that it is very difficult to be broken by hydrogenation (ΔG *N 2 H > 1.00 eV in most cases). 11,16,30,48,69 However, in our work, the PDS is the third hydrogenation step rather than the first hydrogenation step with ΔG max = 0.87 eV along the reaction path 4 (see Fig. 6d).…”
Section: Origin Of the High Activity Of D1-sipmentioning
confidence: 60%
See 2 more Smart Citations
“…Generally, the first hydrogenation step (*N 2 + H + + e − → *N 2 H) is the potential-determining step (PDS) because the triple bond is so strong that it is very difficult to be broken by hydrogenation (ΔG *N 2 H > 1.00 eV in most cases). 11,16,30,48,69 However, in our work, the PDS is the third hydrogenation step rather than the first hydrogenation step with ΔG max = 0.87 eV along the reaction path 4 (see Fig. 6d).…”
Section: Origin Of the High Activity Of D1-sipmentioning
confidence: 60%
“…For instance, experimentally available boron-containing semiconductor compounds, cubic boron phosphide (BP) and boron arsenide (BAs) with modest band gaps of 2.00 eV and 1.50 eV, respectively, theoretically exhibit very high activity and selectivity towards the ENRR; 41 exfoliated few-layer nanosheets of semiconductor black phosphorus experimentally are superior non-metal electrocatalysts for nitrogen reduction. 42 According to previous reports on Si-based NRR catalysts, 17,30,43 we know that p-block Si active sites can activate N 2 and then reduce into NH 3 under electrocatalysis conditions. Therefore, SiP monolayers have the potential of electro-reducing N 2 into NH 3 .…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Similar to B atoms, the Si atom with an electronegativity value of 1.9 is also promising as an electron-deficient center of metal-free carbon materials and enhance the N 2 activation process, and has drawn the attention of researchers recently regarding electrocatalytic N 2 fixation. 82 In fact, the Si element has been proved to be effective for activating some small molecules such as oxygen (O 2 ), carbon monoxide (CO), carbon dioxide (CO 2 ), etc. 83,84 As for the field of the NRR, Sun et al computationally confirmed that the Si atom of SiC can capture and activate N 2 molecules using hexagonal SiC as the model material.…”
Section: Electron-deficient Electrocatalysts Enabling R-donation Effectsmentioning
confidence: 99%
“…A recent theoretical study demonstrated that Si element (doping) is expected to exhibit a great promise for electrochemical NRR under ambient conditions. [278] Moreover, silicene, by itself, interacts very weakly with H 2 molecules. Considering all of these, exploring the feasibility of 2D silicene-based materials as potential electrocatalysts for catalytic NRR would be of great value.…”
Section: Group IVmentioning
confidence: 99%